2019
DOI: 10.1021/acs.iecr.9b04563
|View full text |Cite
|
Sign up to set email alerts
|

Benzene-Induced Crystallization of PPO: A Combined Thermodynamic and Vibrational Spectroscopy Study

Abstract: Sorption of benzene vapor in amorphous poly(2,6-dimethyl-1,4-phenylene) oxide (PPO) has been investigated experimentally at 40 °C by gravimetric analysis and in situ FTIR spectroscopy. This analysis indicates the occurrence of polymer crystallization during sorption when experiments are performed at elevated benzene activities. In fact, absorbed benzene determines a depression of the glass transition temperature of the system and, in turn, an increase of macromolecular mobility that promotes a solvent induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The WAXD pattern (Figure S1a) indicates the presence of c ⊥ -oriented NC α form with a degree of orientation f c ≈ −0.3. Analogous c ⊥ -oriented α form films were obtained by using room temperature guest sorption in thicker amorphous films. , This c ⊥ -oriented NC α form film exhibits a density (0.99 g cm –3 ) being intermediate between those of the starting amorphous film (1.04 g cm –3 ) and of the pure α form (0.93 g cm –3 ). As shown by the photo of Figure a, these films are highly transparent, as generally found for PPO films exhibiting c ⊥ planar orientation of the crystalline chain axis. …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The WAXD pattern (Figure S1a) indicates the presence of c ⊥ -oriented NC α form with a degree of orientation f c ≈ −0.3. Analogous c ⊥ -oriented α form films were obtained by using room temperature guest sorption in thicker amorphous films. , This c ⊥ -oriented NC α form film exhibits a density (0.99 g cm –3 ) being intermediate between those of the starting amorphous film (1.04 g cm –3 ) and of the pure α form (0.93 g cm –3 ). As shown by the photo of Figure a, these films are highly transparent, as generally found for PPO films exhibiting c ⊥ planar orientation of the crystalline chain axis. …”
Section: Resultsmentioning
confidence: 95%
“…Moreover, PPO powders, which generally can be packed in absorption systems only up to an apparent density of 0.3 g cm –3 , also present the drawback of difficult handling, as always occurs for fine particles. Much more handleable are of course self-supporting polymer films, which, however, even for NC polymers and as generally occurs for polymer films exhibit negligible SA (<4 m 2 g –1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation might be the accumulation of the analyte at the interfaces [ 31 ] as a step in the diffusion process, increasing the concentration and the diffusion coefficient. [ 32 ] In fact, it has been reported that the concentration of the sorbed species is higher at the interface of a layer than at its core, increasing diffusivity; [ 33 ] a typical behavior in some amorphous polymers related to their mechanical relaxation. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…The assumption of a temperature-independent k ij is often a good approximation in interpreting equilibrium data for several binary gaseous systems. 11,19,40 Conversely, when lattice-fluid models are applied to condensed phases, a temperature dependence would be expected based on the temperature dependence of mean-field potentials.…”
Section: Nrhb Binary Interactionmentioning
confidence: 99%